Analysis on Location Accuracy for the Binocular Stereo Vision System - Lu Yang; Baoqing Wang; Ronghui Zhang; Haibo Zhou; Rongben Wang (IEEE Photonics Journal)
Binocular stereo vision (BSV) system has been widely used in various fields, such as intelligent manufacture, smart robot, and so on. However, the location accuracy of the current BSV still cannot fully satisfy industry requirements due to lack of a parameters optimization BSV system. In this paper, a high accuracy BSV system is proposed. This is achieved through analyzing the seven parameters of the BSV system, which are classified into two groups: system structure parameters (SSPs) and camera calibration parameters (CCPs). For the SSPs, an improved analysis model is designed to expose the possible errors caused by three parameters. Furthermore, a new correlation model among them is also proposed to analyze the errors caused by their correlation. On the other hand, for the CCPs, the orthogonal experiment model is employed for selecting the optimal combination of the four calibration parameters. Meanwhile, the weight among the four parameters is also analyzed for reducing errors. Finally, the effectiveness of our proposed method is demonstrated by a large number of experiments. It gives a useful reference to the BSV system used in applied optics research and application fields.